HUBUNGAN ANTARA PERSEPSI LANSIA DENGAN KEAKTIFAN DATANG KE POSYANDU DI POLINDES LARANGAN KECAMATAN LARANGAN KABUPATEN PAMEKASAN - Sari Pratiwi Apidianti (Fakultas Ilmu Kesehatan, 2017)
The elderly Posyandu is a health service for the elderly at village or kelurahan level in the working area of ​​the puskesmas. Based on preliminary data obtained in the prohibition village, from 20 elderly it was found that almost half of the elderly were inactive came to posyandu (43.48%). The purpose of this study was to determine the relationship of perception with the liveliness of the elderly came to posyandu in the prohibition village in the work area of ​​Puskesmas Larangan Pamekasan District.Research design with Analytic Case Control where the population is 552 elderly. The sample in this study was obtained from 227 elderly people through Systematic Sampling. The independent variable in this study is the perception of the elderly, while the dependent variable is the elderly activity that comes to posyanduThe result of statistical test x2 count = 67.45 and x2 table = 3,841, because x2 tel > x2 table than HI is accepted and H0 is rejected which means that